Combined three-point bending and axial tension of pressurised and unpressurised X65 offshore steel pipes – Experiments and simulations. (September 2018) - Kristoffersen, Martin; Langseth, Magnus; Børvik, Tore
Abstract: Subsea pipelines are occasionally struck and hooked by objects such as anchors or trawl gear. The initial denting, followed by potential hooking and displacement of the pipeline, give rise to a complex load and deformation history. Transverse displacements cause a simultaneous increase in tensile axial forces, further complicating the load sequence. This study examines the effect of applying one of three different axial loads (zero, constant, and linearly increasing) to a pipe while simultaneously deforming it transversely. The three tests were repeated with an internal pressure of 10 MPa (100 bar), and all tests were recreated numerically in finite element simulations using both iterative (implicit) and non-iterative (explicit) approaches. As expected, adding an axial load increased the pipe's resistance to bending in terms of force-displacement, and the same can be said of including internal pressure. However, a more localised dent was observed in the pressurised pipes, which in turn could affect the onset of failure. The experimental results were well captured by the finite element simulations. Highlights: One of three different tensile axial loads are applied during three-point bending of (un-)pressurised pipes. Internal pressure and axial load increase resistance to bending. Nonlinear finite element simulations are able to represent the global behaviour well. Ovalisation of cross-section is reduced when pressure is included, and plastic strains are reduced. Lagrangian formulation is sufficient to model the internal pressure.